IMMUNO-BIOLOGICAL PROPERTIES OF VAGINAL DISCHARGE IN HEALTHY AND MYCOPLASMOSIS-INFECTED COWS - R. M. Vasiliev; S. V. Vasilieva (Медицинская иммунология)
Genital mycoplasmosis in cows is a disease accompanied by a latent course, which complicates its timely diagnosis and the appointment of adequate therapy. The nonspecific symptomatology of mycoplasmosis, combined with periods of asymptomatic course, leads to the development of functional and morphological changes in the organs of the reproductive system of cows, resulting in infertility. Monitoring studies of livestock farms in the North-West region of the Russian Federation have shown that infection of the genitals of cows with mycoplasmas can be from 20 to 40% of the livestock. Moreover, there is a clear relationship between the high infection rate of the livestock and low reproduction rates. In this regard, livestock enterprises incur significant economic damage. One of the important mechanisms preventing the introduction of various pathogens into the reproductive tract is the resistance of the vaginal mucosa. Among these factors, the most important role is assigned to vaginal autoflora, epithelial desquamation, phagocytosis, acidity of vaginal secretions, the content of immunoglobulins, lysozyme and a number of other nonspecific protective factors in it. We studied the changes in the immuno-biological characteristics of vaginal secretions in the subclinical course of genital mycoplasmosis. Healthy cows with a negative PCR test for Mycoplasma spp. were selected for the study. and infected with Mycoplasma spp., without clinical signs of vaginitis. In both groups of animals, the concentration of hydrogen ions, the activity of lysozyme and immunoglobulins of the classes IgG, IgM, IgA and sIgA were determined in the vaginal secretions. Despite the fact that the persistence of mycoplasmas in the vagina is not accompanied by pronounced clinical signs of vaginitis, but the state of protective factors the mucous membrane undergoes significant changes. The conducted studies made it possible to establish that the long-term presence of mycoplasmas in the vagina of cows is manifested by a significant increase in the concentration of hydrogen ions by 41% and a decrease in the lysozyme activity of vaginal secretions by 2 times, that is, inhibition of the main factors preventing the colonization of mucous pathogenic microflora is observed. In addition, there is a redistribution of classes of immunoglobulins in the vaginal secretion. This is manifested by a significant increase in the content of IgM and sIgA against the background of a tendency towards a decrease in IgA. The noted changes in aggregate create favorable conditions for the introduction of secondary microflora and the development of bacterial-mycoplasma vaginitis, aggravating morpho-functional changes in the reproductive tract and increasing the risk of infertility.